Northport(Malaysia) Bhd : The Impact Of E-Services On Customer Dependencies - Ooi, Sin Cheak (2006)
A survey was conducted to analyze customers' reactions towards Northport's E-services initiatives. This research shows that the E-Services initiatives have positive effects on customer acceptance.